Strategies to Reduce Hospital Mortality in Lower and Middle Income Countries (LMICs) and Resource-Limited Settings - Mullings, Jasneth; Thoms-Rodriguez, Camille-Ann; McCaw-Binns, Affette M.; Paul, Tomlin (IntechOpen, 2019)
This book examines experiences in resource-limited settings, including Low- and Middle-Income Countries (LMICs) and covers a mix of strategies to reduce hospital mortality in these settings. These include population-level and clinical interventions such as health literacy; clinical management guidelines around nutrition; guidelines and protocols for a multi-disciplinary team approach for surgical care; and improving hospital outcomes for elderly patients. The authors argue that robust quality-of-care systems, driven by evidence-based models/frameworks, are relevant in the matrix of solutions. Clinicians, health administrators, policy makers, academics, and students of public health and related disciplines should critically examine these strategies, inclusive of policy and programmatic interventions to reduce hospital mortality across the demographic spectrum in LMICs and other resource-limited settings.